Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Assume $p$ is a prime number such that $p\equiv 1 \pmod3$, and $q=\lfloor \frac{2p}{3}\rfloor$.

If: $$\frac{1}{1\cdot2} +\frac{1}{3\cdot4} +\cdots+\frac{1}{(q-1)\cdot q} =\frac{m}{n}$$

For some integers $m,n$, what is the proof that $p\mid m$

share|cite|improve this question
I changed the dots to multiplications, I hope that is what you ment. – Simon Markett Aug 25 '12 at 11:08
Also is it clear that $q-1$ is odd, or could the sum possibly end with $\frac{1}{q(q+1)}$? – Simon Markett Aug 25 '12 at 11:11
@SimonMarkett $q-1$ is odd since $p$ is of the form $3k+1$, so $q = \lfloor (6k+2)/3 \rfloor = \lfloor 2k+2/3 \rfloor= 2k.$ – Ragib Zaman Aug 25 '12 at 11:14

Let $p=3k+1$ and $H_n$ denote the n-th harmonic number. Since $\displaystyle \frac{1}{n(n+1)} = \frac{1}{n} - \frac{1}{n+1}$ (1) the sum in the question is $$\displaystyle \sum_{i=1}^q \frac{ (-1)^{i+1} }{i} = H_{2k}-H_k.$$

Working in mod $p$, we add $p$ to the denominator of each term in $H_k$ : $$ H_{2k} - H_k \equiv H_{2k} + \sum_{i=1}^k \frac{1}{p-i} = H_{p-1} =\frac{1}{2}\sum_{i=1}^{p-1} \left( \frac{1}{i} + \frac{1}{p-i}\right)\equiv \frac{1}{2}\sum_{i=1}^{p-1} \left( \frac{1}{i} + \frac{1}{-i}\right)=0. $$

proving the result.

Using (1) we see that $$\frac{1}{1\cdot2} +\frac{1}{3\cdot4} +\cdots+\frac{1}{(q-1)\cdot q} = \frac{1}{1} - \frac{1}{2} + \frac{1}{3} \cdots + \frac{1}{q-1} - \frac{1}{q}.$$

The series is almost like a Harmonic number but it has alternating signs, so we add and subtract 2*even terms:

$$\frac{1}{1} - \frac{1}{2} + \frac{1}{3} \cdots + \frac{1}{q-1} - \frac{1}{q} = \left( 1+ \frac{1}{2} + \cdots + \frac{1}{q} \right) -2 \left( \frac{1}{2} + \frac{1}{4} + \cdots + \frac{1}{q} \right).$$

The factor of 2 cancels with the denominator of every term in the second bracket. Remembering that $q=2k$ gives $$ \left( 1+ \frac{1}{2} + \cdots + \frac{1}{2k} \right) - \left( 1 + \frac{1}{2} + \cdots + \frac{1}{k} \right)= H_{2k} - H_k.$$

share|cite|improve this answer
Great answer! I'd prefer to finish $H_{p-1}=\sum_{i\in(\mathbf Z/p\mathbf Z)^\times}i^{-1}=\sum_{i\in(\mathbf Z/p\mathbf Z)^\times}i=0\in\mathbf Z/p\mathbf Z$, but that really just a matter of taste. – Marc van Leeuwen Aug 25 '12 at 15:16
@Marc That is a very nice proof of that fact, I wish I'd thought of that! – Ragib Zaman Aug 25 '12 at 15:30
Is that mean $m=0$ ? – Frank Aug 26 '12 at 5:45
@MohammedAl-mubark It means $m=0$ working mod $p$, which means $m$ is divisible by $p.$ – Ragib Zaman Aug 26 '12 at 6:41
Yes , i understand what you are saying,may be i should think before writing anything . – Frank Aug 26 '12 at 6:58

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.